Unlocking Vocabulary: How Podcast Listening Boosts Language Skills in Lampung Vocational School Students - Nawawi, Muhammad (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
Many scholars believe that students who regularly listen to English podcasts receive positive feedback in learning English. This study aims to prove this belief and explore the relationship between students' podcast listening habits and their vocabulary skills. The researcher used a quantitative method with a correlational research approach. The sample was chosen using purposive sampling. A questionnaire was used to collect data on students' podcast listening habits, and a test was administered to assess their vocabulary mastery. The Pearson Product Moment formula was used for data analysis. The results showed that r_count (0.458) is greater than r_table (0.263), indicating a positive and moderate correlation between podcast listening and vocabulary mastery. The significant F change was 0.000, which is less than 0.05, further supporting the positive correlation. Therefore, it can be concluded that there is a moderate correlation between students' habit of listening to English podcasts and their vocabulary mastery, meaning the more they listen, the better their vocabulary becomes.